Nature Symbolism in Religious Music - Agnieszka Sojka (Nicolaus Copernicus University in Toruń, 2011)
The objective of the research is to show that the use of nature imagery is a very important aspect in religious songs. These images and symbols such as valleys, mountains, and flowers are used to describe the holy figures including Jesus, Mary, Joseph, God the Father, and the Holy Spirit. The analysis of lyrics in a variety of Polish religious songs proves that nature is an important and underlying theme in these texts.